Exploring final year dental students’ attitudes toward and understanding of reflection and reflective practice in the Conservative Dentistry Clinics at a South African dental school - Cloete, Colleen Carol Anne (Stellenbosch : Stellenbosch University, 2020)
Thesis (MMed)--Stellenbosch University, 2020.